Implementasi Metode MAUT Dalam Pemilihan Aplikasi Pembuatan Media Pembelajaran Dimasa Pandemi Covid 19 - Pradana, Ari; Manik, Lastri; Syahrizal, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Corona Virus disiase 2019 (covid 19) is an infectious disease caused by SARS-CoV-2 a type of Corona virus. This virus is transmitted through physical contact and causes symptoms of respiratory problems, colds, fever, dry cough, and attacks the human physical immunity. covid 19 has disrupted the activities of daily human life, including in the field of education. To prevent the spread of covid 19 the government proposes that during the covid 19 pandemic the teaching and learning process takes place online or online. In the online learning process so that students are more active, creative and enthusiastic, a system is needed decision support that can determine and choose the application of learning media during the covid 19 pandemic, a decision support system that can solve the problem using the MAUT (Multi Attribute Utility Theory) method and produce an appropriate decision based on the results of the data obtained such as alternatives and the criteria so as to produce a decision, namely the application of the best learning media in the era of covid 19, namely the Sony Vegas Pro application with a score of 0.9025.